Necessidades de conforto da pessoa que vive com AIDS: uma pesquisa-cuidado com base no modelo teórico de Katharine Kolcaba - Lima, Kely Regina da Silva (2012)
This investigation is a research-care, with qualitative approach whose research question was: What are the comfort needs of the person who live with aids? The objectives were to understand in the experiences of comfort and discomfort of a person with AIDS, their comfot needs and to develop measures of individual and collective comfort needs to needs present in the meetings of the being-researched with the being-researcher. We selected people diagnosed with aids, irrespective to be man or woman and being considered as exclusion touchstones are younger than 18 years; instability of the feature clinical or involvement, at the time of interview, for respiratory infections transmitted or cognitive disorders. The informations collected were analyzed based on the theoretical reference of the Katharine Kolcaba’s Theory of Comfort, as from which it was possible to identify the needs of comfort, linked to studies of relief, tranquility and transcendence, in the physical, psychospiritual, sociocultural and environmental dimensions. The results showed that the person who live with aidshave needs of comfort that when related to physical context refer to the sensations of the body when in internment or in the discovery of the disease. In the psychospiritual context, are deriving to sadness, fear and awareness about living with an incurable disease. When referring to the sociocultural context, arise from interpersonal and family relationships and financial issues or related to work. In the environmental context, the needs refer to environments where these people receive care within the health service. These needs of health care or needs of comfort identified demanded individual care, which were directed to those which were prevalent at the time of interview, and a planning for care based on a need of comfort displayed in all persons investigated, which we call Workshop of care of the person living with AIDS about opportunistic infections. This study points to the need for qualification of teams so they can take care of the person who lives with aids and of their families too. It also considers how important the strengthening of institutional policies for the health services and special attention to the training of the nurse as a professional of reference in the satisfaction of comfort the person who lives with aids.